2015
DOI: 10.5530/pc.2015.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of the zoonotic bacteria Bacillus anthracis by high antioxidant Australian plants: New leads for the prevention and treatment of anthrax

Abstract: Introduction: Anthrax is severe acute disease caused by Bacillus anthracis infections. If untreated, it often results in mortality. High antioxidant plant extracts have documented therapeutic properties as general antiseptics, inhibiting the growth of a wide variety of bacterial species. This study examines the ability of selected high antioxidant Australian plant extracts to inhibit B. anthracis growth. Methods: Solvent extracts were prepared using various high antioxidant Australian fruits and herbs and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Many high antioxidant fruits and herbs have been reported to have good antibacterial activities. [12][13][14][15][16][17][18][19]21,33,36 Given the high antioxidant capacities and 'superfood' status of acai, cacao and maca, surprisingly few studies have examined their ability to inhibit the growth of pathogenic bacteria. Indeed, whilst multiple anecdotal reports are available, we were unable to find any scientific studies screening acai, cacao or maca extracts for the ability to inhibit the growth of P. mirabilis, K. pneumoniae, A. baylyi or P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many high antioxidant fruits and herbs have been reported to have good antibacterial activities. [12][13][14][15][16][17][18][19]21,33,36 Given the high antioxidant capacities and 'superfood' status of acai, cacao and maca, surprisingly few studies have examined their ability to inhibit the growth of pathogenic bacteria. Indeed, whilst multiple anecdotal reports are available, we were unable to find any scientific studies screening acai, cacao or maca extracts for the ability to inhibit the growth of P. mirabilis, K. pneumoniae, A. baylyi or P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the inhibitory activity of many plant extracts against a wide panel of pathogenic bacteria. [12][13][14] Furthermore, potent growth inhibition has been reported for several high antioxidant fruits [15][16][17] and culinary herbs. 18 Particularly noteworthy, Terminalia ferdinandiana (Kakadu plum), Tasmannia lanceolata (mountain pepperberry) and several Syzygium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial screening was achieved using a modified peptone/yeast extract (PYE) agar containing: 1 g/L peptone, 1.5 g/L yeast extract, 7.5 g/L NaCl, 1 g/L ammonium persulfate, 2.4 g/L HEPES buffer (pH 7.5) and 16g/L bacteriological agar as previously described. 27 The S. putrefaciens and S. loihica cultures were incubated at 30 o C for 24 h. The S. baltica and S. frigidimarina cultures were incubated at 15 o C for 72 h. All stock cultures were subcultured and maintained in PYE media at 4 o C. The media nutrient components were supplied by Oxoid Ltd., Australia.…”
Section: Qualitative Phytochemical Studiesmentioning
confidence: 99%
“…32,33 Briefly, the plant extracts were diluted in deionised water and tested across a range of concentrations. Discs were impregnated with 10 µL of the extract dilutions, allowed to dry and placed onto inoculated plates.…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%